Strategic planning of urban transportation system based on sustainable development dimensions using an integrated SWOT and fuzzy COPRAS approach - S.M. Hatefi (Global Journal of Environmental Science and Management)
Today, urban transportation has attracted urban planners’ and researchers' attention because of air and noise pollution problems associated with it. In Shahrkord city in Iran, no plans have been made for sustainable transportation, and the available poor transportation infrastructure is not responsive to the growing population of the city. This issue has inflicted the city with serious problems, including environmental pollution, traffic jams, and car accidents. Therefore, it is necessary for urban managers and planners to conduct necessary planning and analysis for the development of urban transportation system through a strategic perspective. In this study, the strengths and weaknesses as well as the opportunities and threats of Shahrkord transportation system are identified using strength, weakness, opportunity, threat (SWOT) analysis. Status of the city's transportation system is determined through evaluation of internal and external factors. The results of SWOT analysis and the matrix of internal and external factors indicate that the internal and external evaluation factors are equal to 2.330 and 3.367, respectively, which means that Shahrekord transportation system holds a conservative situation. Considering the identified status, several strategies are proposed to improve the status quo. Finally, the proposed strategies are evaluated based on sustainable development indices, namely economic, environmental, and social indices, by using the fuzzy complex proportional assessment (COPRAS) method. The results show that the best proposed strategy is attraction of private investors to set up pedestrian bridges equipped with escalators and the concession of using them for the establishment of environmental advertisement.